There we found brethren a history of Assemblies of Brethren in New Zealand - Lineham, Peter J. 1951- (Palmerston North, NZ Gospel Publishing House, 1977)
Includes bibliographical references and indexes.
Brethren writer.
Keywords: Brethren movement -- New Zealand -- history